(untitled) (Medico Legal Update, 2022)
Background: Till now no significant study has been done in homicide cases related to the tribal communities of the Bastar region, our approach has been to extensive study of the tribal communities, their life pattern towards the arms, and analysis of the homicidal committed in the tribal communities Objective: the objective of the study was to study the pattern of homicidal cases in the tribal communities of Bastar in a community wise scale so that necessary steps can be taken to prevent homicide in communities which has high scale of homicidal cases. Material and Method: The data of postmortem reports of all cases of homicidal deaths of tribals of Bastar region Chhattisgarh occurred in 11 years (2011 to 2021), which had been brought to the mortuary of Forensic Medicine department. Results: Out of total of 122 cases evaluated, it consisted predominantly of male population of the age 31-40 years, Maximum number of homicidal cases were from Firearm injury=27 cases, Axe injury sustained stood 2nd= 22 cases. Maximum cases were found in the year 2015=16 cases. Maximum cases occurred in the Month of August=24 cases. Conclusion: In our study we have found that Madia community followed by Maria community has most of the leading cases, government need to more emphasize on them to prevent cases from occurring. Homicidal deaths among tribals was mainly due to firearm injury, main factor for it was Naxalite and Maoist movement, which is predominant in Bastar region